The Role of Black Soldier Fly Maggots in Household Waste Processing to Organic Fertilizer - Rohmah, Ranindya Nur; Safriana, Marsita; Rifina, Areta Risky; Salsabila, Aviana; Puspita, Amel Bela; Naufal, Muhamad Labib; Jaelani, Farrel Ahsan; Attar, Faisal Denand; Ummah, Shofiatul; Faizah, Nabila Hasna; Almanan, Dzakariyo Zaqfan; Randikaparsa, Irawan; et al. (Proceedings Series on Social Sciences & Humanities, 2025)
Organic waste management in Indonesia remains a major challenge, with most household waste not being managed optimally. One potential solution is the use of Black Soldier Fly maggots (Hermetia illucens) through a bioconversion method to convert organic waste into high-quality organic fertilizer. This community service activity was carried out in Pagenteran Village, Pulosari District, Pemalang Regency, using the Community Rural Participatory (CRP) method, which actively involved the community in all stages, from problem identification and planning to implementation. Outreach was conducted with 30 local farmers to provide knowledge about maggot cultivation and the process of making organic fertilizer from kasgot. The results of the activity showed an increase in community understanding regarding the benefits of maggots in reducing the volume of organic waste, increasing soil fertility, and providing an alternative protein-based animal feed. Participants also stated that this activity was relevant to their needs and was able to provide practical solutions for sustainable household waste management.